Supervision for independence? - Lindenskov Tamborg, Andreas (Improving University Science Teaching and Learning, 2023)
In this report, I reflect upon my UP project concerning supervision of two master thesis students. The aim of my UP project was to supervise the students with a specific purpose on allowing them to build independence. To do so, I informed my supervision practice by insights from research literature about higher education supervision. After the students’ exams, I conducted an interview study to investigate their perception of building independence in relation to their thesis work, and the role of them as students and me as supervisor in that process.